Prevalence and factors associated with effective helmet use among motorcyclists in Mysuru City of Southern India - Naveen Kikkeri Hanumantha Setty; Gautham Melur Sukumar; Sumanth Mallikarjun Majgi; Akhil Dhanesh Goel; Prem Prakash Sharma; Manasa Brahmanandam Anand (Komiyama Printing Co. Ltd, 2020)
Abstract Background Helmet use reduces the risk and severity of head injury and death due to road traffic crash among motorcyclists. The protective efficacy of different types of helmets varies. Wearing firmly fastened full-face helmet termed as effective helmet use provides greatest protection. This study estimates the prevalence and factors associated with effective helmet use among motorcyclists in Mysuru, a tier II city in Southern India. Methods Cross-sectional road side observational study of 3499 motorcyclists (2134 motorcycle riders and 1365 pillion riders) at four traffic intersections was done followed by interview of random sample of 129 of the above riders. Effective helmet use proportion and effective helmet use per 100 person-minute of observation was calculated. Multivariate logistic regression analysis was done to identify factors associated with effective helmet use. Results Prevalence of effective helmet use was 28 per 100 riders and 19.5 per 100 person-minute of observation in traffic intersections. Prevalence rates of effective helmet use was higher among riders (34.5% vs pillion riders 18.1%), female riders (51.3% vs male riders 26.8%), and male pillion riders (30.5% vs female pillion riders 13.7%). Riders commuting for work and school and those ever stopped by the police in the past 3 months had significantly higher odds of effective helmet use. Conclusion Despite helmet use being compulsory by law for motorcyclists, the effective helmet use was low in Mysore. Strict enforcement and frequent checks by the police are necessary to increase the effective helmet use.